Hydrogels empowered mesenchymal stem cells and the derived exosomes for regenerative medicine in age-related musculoskeletal diseases - Lixin Liu; Siwen Chen; Yantao Song; Longwei Cui; Yiman Chen; Jiangli Xia; Yibo Fan; Liqun Yang; Lina Yang (Pharmacological Research)
As the population ages, musculoskeletal diseases (MSK) have emerged as a significant burden for individuals, healthcare systems, and social care systems. Recently, regenerative medicine has exhibited vast potential in age-related MSK, with mesenchymal stromal cells (MSCs) and their derived exosomes (Exos) therapies showing distinct advantages. However, these therapies face several limitations, including issues related to ensuring stability and effective distribution within the body. Hydrogels, acting as an ideal carrier, can enhance the therapeutic effects and application range of MSCs and Exos derived from MSCs (MSC-Exos). Therefore, this review comprehensively summarizes the application progress of MSCs and MSC-Exos combined with hydrogels in age-related MSK disease research. It aims to provide a detailed perspective, showcasing the functional enhancement of MSCs and MSC-Exos when incorporated into hydrogels. Additionally, this review explores their potential and challenges in treating age-related MSK diseases, offering references for future research directions and potential innovative strategies.